Studie norem řízení pro výrobní organizaci - Altmanová, Hana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato diplomová práce se zaměřuje na analýzu výkonových norem a využitelnost klíčové technologie ve výrobní firmě KLEIN automotive s.r.o. Práce následně navrhuje řešení výpočtu norem dle nových metod pro konkrétní technologii firmy. Řešení zohledňuje nejnovější trendy ve výpočtu výkonových norem a ve sledování výkonu při dosažení ekonomické návratnosti.

This diploma thesis aims on the analysis of performance standards and the usability of key technology in the production company KLEIN automotive s.r.o. Subsequently the thesis suggests a solution for calculating standards according to new methods for a particular technology of the company. The solution takes into the latest trends in performance standards calculation and performance monitoring while achieving economic returns.
The Study Management Standards for the Manufacturing Organization
Keywords: výkon; strojní čas; OEE; plánování; tvorba norem; performance; machine time; OEE; planning; development of standards